The Effect Of Grammar In Some Types Of Badia - يونس يونس علي; سليمان بثينة; إبراهيم عمّار حسّان (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This paper attempts to clarify the relationship between the rules of Arabic grammar and its structural methods on the one hand and some types of badia familiar in Arabic rhetoric on the other hand. It is divided into three axes, each revolving around aspecific point, and it deals with a number of arts that it clearly noticed that aspecific grammatical rule contriputed to its formation, indicating the effect of that rule on the aesthitics of those types, as well as other types that are distingushed by their adoption of syntactic tools and structural formulas that enrich their semantic side. Its rhetorical effects are evident on the respient, and it ends with an examination of some types that are based on parallels between grammatical structures, revealing the musical effects that such parallelism creats in creative textes, aiming from behind that to reveal more aesthetic aspects of Arabic grammar.